The Existence of an Integrated Salafi-Based Islamic School in Padang City - Saklaili, Sakinah; Satria, Rengga (EDUMALSYS Journal of Research in Education Management, 2023)
This study aims to determine the existence of an integrated Salafi-based Islamic school in one of the schools in the city of Padang. The method used in this study is qualitative with a focus on phenomenology. Data collection was carried out in this study using observation techniques, interviews, and documentation. Information was obtained through interviews with two informants in this study including the principal and teacher of the Integrated Islamic Elementary School Dar el-Iman Foundation. The data analysis technique used is using the data analysis model of Miles and Huberman which starts with data collection, data reduction, data presentation, and concluding. Apart from that, to test the validity of the data, this study used a validity test. The validity test used in this study is triangulation testing which is a data-checking technique. Where the researcher will re-examine the data obtained with different techniques for the same person. The results of this study found that the existence of formal institutions under the auspices of the Dar El Iman Foundation was very positive among the community, especially in the city of Padang. This is evidenced by the application of the curriculum and methods applied to elementary schools at the Dar El-iman integrated Islamic school foundation that can have a positive impact on students. In addition to creating a learning environment that is balanced between academic knowledge and character development based on Islamic values.